Microphysical detection of nano-ice nuclei to ice crystals: a platform for ice nucleation research - Devendra Pal; Ryan Hall; Yevgen Nazarenko; Leonard Barrie; Parisa A. Ariya (npj Climate and Atmospheric Science)
Abstract Atmospheric ice nucleation plays a crucial role in cloud formation, precipitation, and climate dynamics. However, the physicochemical properties of submicron ice nucleating particles (INPs) remain poorly understood, and distinguishing between nano- to micron-sized ice crystals and supercooled droplets in cloud microphysical processes remains a significant challenge. Here, we present the first detection of nano-sized ice crystals (390 nm) along with their physical properties using a portable platform for ice nucleation that integrates the McGill Real-time Ice Nucleation Chamber (MRINC) with advanced holographic microscopy and aerosol sizers. This platform enables real-time detection and differentiation of ice crystals and supercooled droplets, providing microphysical information into their spherical or non-spherical morphology, surface roughness, and phase characteristics, particularly for ice particles smaller than 500 nm. Automated algorithms facilitate the differentiation of individual and aggregated ice crystals within a size range of 390 nm to 100 µm, supporting time-resolved analyses of ice nucleation processes. Surface roughness (Rt, Ra) measurements and 3D structural data offer critical insights into light scattering and radiation interactions, with smaller ice crystals (<1 µm) exhibiting higher roughness and enhanced multidirectional scattering. Validation through computational fluid dynamics simulations and experiments demonstrates platform ability to differentiate silver iodide-nucleated ice crystals from supercooled droplets and to monitor aerosol growth, advancing our understanding of aerosol-cloud-radiation interactions.